DEMOGRAPHIC CHARACTERISTICS AND SELF-EAR-CLEANING RELATED EFFECTS AMONG ADULTS ATTENDING PUBLIC HEALTH CLINICS IN NORTH-CENTRAL NIGERIA: A VIDEO-OTO-ENDOSCOPIC STUDY - Ochin Ngozika Georgiana; G.A. Amuga; A. I. Akyala; Ochin Chiamaka Georginia; tiku Adams Shaibu (INTERNATIONAL JOURNAL OF PUBLIC HEALTH RESEARCH AND DEVELOPMENT, 2026)
Self-ear cleaning; the insertion of objects into the ear canal to remove cerumen, is a globally prevalent practice despite well-documented risks including otitis externa, tympanic membrane perforation, and cerumen impaction. Most existing evidence relies on self-reported data without objective clinical verification. Furthermore, the relationship between demographic characteristics and objectively confirmed ear health consequences of this practice remains poorly characterised. This study examined whether gender, age, occupation, and educational status are associated with video-oto-endoscopically confirmed ear effects related to self-ear-cleaning among adults attending two public health clinics in North-Central Nigeria. A descriptive cross-sectional study was conducted among 553 adults aged 20–60 years attending the Ministry of Defence Headquarters Clinic, Abuja, and the Nasarawa State University Keffi Medical Centre, Nigeria. Participants completed a structured questionnaire capturing sociodemographic characteristics and subsequently underwent video-oto-endoscopic examination performed by trained ear, nose, and throat personnel. Findings were recorded on a structured tally sheet. Pearson’s chi-square test assessed associations between sociodemographic characteristics and the presence of self-ear-cleaning-related ear effects, with statistical significance set at p < 0.05. Among 553 participants (265 males, 288 females), 362 (65.5%) exhibited video-oto-endoscopically confirmed ear conditions attributable to self-ear-cleaning practices. Prevalence was comparable across demographic subgroups: males 67.2% vs. females 63.9% (χ² = 1.124, p = 0.289); age groups 64.8–65.9% (χ² = 1.502, p = 0.472); military personnel 65.3% vs. civilians 65.5% (χ² = 0.115, p = 0.735); and educational strata (χ² = 1.591, p = 0.451). None of the examined demographic characteristics were significantly associated with the presence of ear effects. Self-ear-cleaning-related ear effects, objectively confirmed through video-oto-endoscopy, are highly prevalent among adults attending public health clinics in North-Central Nigeria, affecting all demographic subgroups with statistically comparable frequency. Demographic characteristics are poor predictors of self-ear-cleaning-related harm, suggesting that behavioural, cultural, and habitual factors — rather than sociodemographic profile — are the primary drivers. Public health interventions should adopt population-wide behavioural change approaches addressing entrenched misconceptions about ear hygiene, targeting all demographic segments equally.